On “Rationality” in Criminal Law - Janiszewski, Bogusław (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Rozważania o “racjonalności” w dziedzinie prawa karnego by Bogusław Janiszewski, published origi-nally in Polish in “Ruch Prawniczy, Ekonomiczny i Socjologiczny” in 1996. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.